Сучасний стан та перспективи розвитку кондитерської промисловості України - Чайкова, Олена Ігорівна; Мірошніченко, Юлія Юріївна (НТУ "ХПІ", 2015)
У статті проведено аналіз основних факторів, які впливають на розвиток однієї з найрозвинутіших галузей харчової промисловості України – кондитерської галузі. Розглянуто основних виробників українського внутрішнього кондитерського ринку та виявлено їх основних конкурентів – іноземних виробників. Досліджено зміни в об’ємах експорту продукції та визначено чинники найбільшого впливу на нього, а також описані основні тенденції та перспективи розвитку кондитерської галузі у найближчий час. Надано рекомендації, які допоможуть стабільно утримувати свої позиції на ринку українським виробникам.

The article analyzes the main factors influencing the development of one of the most developed food industries Ukraine – confectionery industry. The basic Ukrainian producers of domestic confectionery market and found their main competitors – foreign manufacturers. The changes in the volumes of exports and identifies the factors most influence on him. Also describes the main trends and prospects of the confectionery industry in the near future. The recommendations that will help to keep stable its market position Ukrainian producers. The study leads to the following conclusions: - The investment climate shaping the investment attractiveness of the country; - Ukraine's place in the World Bank study ranked the index "Doing Business" in the context of individual components in 2013 improved by 15 points; - Investor countries Ukraine, which account for 55% of total investments were Cyprus, Germany and the Netherlands; - Most of attracted foreign investments accounted for Ukrainian industry, as well as financial institutions and insurance activities.
The current state and prospects of the confectionery industry Ukraine
Keywords: експорт; поставки; стратегічний план; конкуренція; виробництво; export; supply; strategic plan